The deposition of type II-S Jordan oil shale in the context of Late Cretaceous source rock formation in the Eastern Mediterranean realm. Insights from organic and inorganic geochemistry and petrography. (February 2023) - Grohmann, S.; Littke, R.; Abu-Mahfouz, I.; Gaus, G.; Klaver, J.; Thüns, N.; Schulte, P.; Patzek, T.; Vahrenkamp, V.
Abstract: This study provides a detailed geochemical and petrographic investigation of 22 Upper Cretaceous Jordan Oil Shale (JOS) samples obtained from various wells distributed across Jordan. The JOS is generally characterized by high amounts of organic matter with total organic carbon (TOC) contents of 10–29 wt%, high carbonate contents of 15–75 wt%, and variable biogenic SiO2 contents of 1–50 wt%. The organic matter is oil-prone, reflected by a clear predominance of liptinite macerals and Rock-Eval Hydrogen Index (HI) values of 608–1078 mg HC/g TOC. In terms of elemental composition, bulk and molecular organic geochemistry and petrology, the JOS is similar to other age-equivalent organic-rich rocks from the Eastern Mediterranean. Primary bioproductivity was probably controlled by a Late Cretaceous upwelling event that affected the whole region. Low Pr/Ph ratios <0.5 indicate that organic matter preservation was not only controlled by the formation of an upwelling-related oxygen minimum zone but also by further oxygen depletion in isolated sub-basins. This setting led to vulcanization of kerogen; proven by a positive correlation between calculated organic sulfur contents and the amount of thiophenes generated during Curie-point pyrolysis. Although the thermal maturity is low (Tmax values < 430°C), significant amounts of hydrocarbons (up to 30 kg HC per ton of rock) are present within these rocks. The present bitumen fraction shows high concentrations of asphaltenes (10–65%) and NSO compounds (30–85%) with higher contributions in samples with the lowest thermal maturities. The relative contributions of aliphatic and aromatic compounds are correspondingly low, but increase with higher thermal maturities. Kinetic parameters suggest that isothermal pyrolysis at 350°C might be already enough to artificially convert 80% of the reactive kerogen within about one day, making the JOS a potential target for oil shale retorting. Highlights: Extensive geochemical characterization of Late Cretaceous Jordan Oil Shale (JOS). The JOS can be partly linked to the Late Cretaceous Upwelling period. Type II-S source rock with high TOC content formed under euxinic conditions. Although thermally immature, the JOS generated significant amounts of heavy oil. Petroleum generation kinetics suggest low temperatures for shale retorting.